Book Reviews - v, William D.; Hayn, Ileen P. (Columbia Journal of Environmental Law, 2020)
THE POLITICS OF CANCER. By Samuel S. Epstein, M.D. San Francisco: Sierra Club Books, 1970. Pp. 583. CURRENT ISSUES IN U.S. ENVIRONMENTAL POLICY. Edited by Paul R. Portney. Baltimore: The Johns Hopkins University Press, 1978. Pp. 207.